2020
DOI: 10.1186/s12889-020-08538-3
|View full text |Cite
|
Sign up to set email alerts
|

HIV care continuum characteristics among people with opioid use disorder and HIV in Vietnam: baseline results from the BRAVO study

Abstract: Background: Little is known about patient characteristics that contribute to initiating antiretroviral therapy (ART) and achieving viral suppression among HIV people with opioid use disorder in Vietnam. The primary objective of this analysis was to evaluate associations between participant characteristics and the critical steps in the HIV care continuum of ART initiation and HIV viral suppression among people with opioid use disorder and HIV in Vietnam. Methods: We assessed baseline participant characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…While mental health symptoms are independently associated with poorer HIV outcomes, alcohol use can also accelerate HIV progression through a number of mechanisms. High levels of alcohol use do not only negatively impact ART adherence and response to medication but can also lead to compromised liver function and liver diseases [35][36][37][38][39][40][41][42]. Therefore, mental health symptoms and high levels of alcohol use can substantially increase the risk of treatment failure among PWH [43].…”
mentioning
confidence: 99%
“…While mental health symptoms are independently associated with poorer HIV outcomes, alcohol use can also accelerate HIV progression through a number of mechanisms. High levels of alcohol use do not only negatively impact ART adherence and response to medication but can also lead to compromised liver function and liver diseases [35][36][37][38][39][40][41][42]. Therefore, mental health symptoms and high levels of alcohol use can substantially increase the risk of treatment failure among PWH [43].…”
mentioning
confidence: 99%
“…We then divided adherence scores into two categories; imperfect adherence (defined as scores 1–8) and perfect/high adherence (defined as scores 9–10), similar to previous studies categorization of HIV viral load, including the BRAVO trial conducted in Vietnam. 19 ART adherence measurements were based on self-report (note that previous studies have highlighted the reliability of self-reported ART adherence measurements, 20 and our community based organization members (CBOs) worked with our participants to ensure accurate ART adherence reporting).…”
Section: Methodsmentioning
confidence: 99%
“…They were: low levels of education, the requirement to have an identity card, treatment schedules that conflict with work schedules, and the policy of subsidizing the cost of running the clinics. A recent report assessing associations between participant characteristics and critical steps in the HIV care continuum of the BRAVO (Buprenorphine to Improve HIV Care Engagement and Outcomes) study suggested the need for an intervention such as integrating opioid use disorder treatment in HIV treatment settings, and at the same time highlighted the essential of family and social relationships in HIV viral suppression (King et al, 2020). Korthuis et al (2021) pointed out improved HIV viral suppression in participants at HIV clinics that integrated either buprenorphine plus naloxone or methadone maintenance therapy, and that the retention in either antiretroviral treatment or opioid use disorder medications of participants could influent the appearance of serious adverse events and deaths.…”
Section: Drug Intervention and Opportunities For Evidencebased Treatments For Drug Addiction In Vietnammentioning
confidence: 99%